Spontaneous Bacterial Peritonitis in Egyptian and Saudi Patients with Liver Cirrhosis - Hassan-Elbanna M.A. Younus,; Asif A.M. Jiman-Fatani, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to investigate spontaneous bacterial peritonitis in Egyptian and Saudi patients with liver cirrhosis and changes of their laboratory indicators in assisting with in their diagnosis and treatment. Seventy Egyptian and Saudi cirrhotic patients with spontaneous bacterial peritonitis and 30 patients with liver cirrhosis alone were investigated. In addition to liver function tests, ascitic fluid specimens were investigated for cytological, biochemical and bacteriological changes. Results revealed that 12 (17.1%) of spontaneous bacterial peritonitis patients showed culturenegative neutrocytic ascites, while 58 (82.9%) patients were culture-positive. Hence, their occurrence was more frequent in old male patients without significant difference regarding the nationality. These patients presented with fever, abdominal pain, high activity of liver enzymes and high serum levels of bilirubin and low of proteins; albumin and glucose. Their ascitic fluids showed a high polymorph nuclear cell count > 250 cells/mm3. Microorganisms isolated were Enterobacteriaceae (e.g. Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis), Staphylococcus-aureus, Staphylococcus epidermidis and Enterococcus faecalis. Blood culture bottle method showed more positive result than that obtained by conventional culture method. Most of the isolated microorganisms showed sensitivity to Cefotaxime while Enterococcus faecalis showed sensitivity to meropenem.